Graphite negative electrode active material, preparation method thereof, secondary battery containing graphite negative electrode active material, and electric device containing graphite negative electrode active material

By controlling the powder compaction density and surface defect degree of graphite negative electrode active material, the compatibility of energy density and rate performance in secondary batteries is solved, and the consideration of high energy density and excellent rate performance is achieved.

CN119852341APending Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202311679523.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-07
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art is difficult to take into account both high energy density and excellent rate performance in secondary batteries.

Method used

By controlling the powder compaction density of graphite negative electrode active material at a pressure of 49000N and the specific peak intensity ratio Id/Ig in the Raman spectrum, the material has a high powder compaction density and an appropriate degree of surface defects.

Benefits of technology

The secondary battery has achieved high energy density and excellent rate performance, improving the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852341A_ABST
    Figure CN119852341A_ABST
Patent Text Reader

Abstract

The invention provides a graphite negative electrode active material, a preparation method thereof, a secondary battery containing the graphite negative electrode active material and an electric device. The powder compaction density of the graphite negative electrode active material under the pressure of 49000N is greater than or equal to 1.60 g / cm < 3 >, and the ratio Id / Ig of the peak intensity Id of 1250cm <-1 > to 1500cm <-1 > to the peak intensity Ig of 1500cm <-1 > to 1650cm <-1 > in a Raman spectrum of the graphite negative electrode active material is greater than or equal to 0.15. The graphite negative electrode active material can give consideration to both the energy density and the rate capability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a graphite negative electrode active material and a preparation method thereof, a secondary battery containing the same, and an electrical device. Background Art

[0002] With the development of electric vehicles, large-scale energy storage systems and other fields, the market has put forward higher and higher requirements for the energy density and rate performance of energy storage devices. However, from a technical perspective, it is difficult to achieve perfect compatibility between energy density and rate performance. Summary of the invention

[0003] The present application is made in view of the above-mentioned problems, and its purpose is to provide a graphite negative electrode active material, and a secondary battery prepared by using the graphite negative electrode active material can take into account both the energy density and rate performance of the battery.

[0004] The first aspect of the present application provides a graphite negative electrode active material, wherein the powder compaction density of the graphite negative electrode active material under a pressure of 49000N is greater than or equal to 1.60g / cm 3 ; 1250cm in the Raman spectrum of graphite negative electrode active materials -1 Up to 1500cm -1 The peak intensity Id and 1500cm -1 Up to 1650cm -1 The peak intensity Ig ratio Id / Ig is greater than or equal to 0.15.

[0005] The graphite negative electrode active material has a high powder compaction density under a pressure of 49000N, which can improve the compaction density of the negative electrode film layer, thereby further improving the energy density of the secondary battery. At the same time, the Id / Ig of the graphite negative electrode active material indicates the degree of defects on the surface of the material. When Id / Ig is within the above range, the surface of the negative electrode material has a large number of defects, which can promote ion adsorption and bonding, improve the transmission performance of active ions, and improve the rate performance of the battery.

[0006] In summary, by controlling the powder compaction density and Id / Ig of the graphite negative electrode active material under a pressure of 49000N within a suitable range, the secondary battery can have both high energy density and excellent rate performance.

[0007] In any embodiment, the powder compaction density of the graphite negative electrode active material under a pressure of 49000N is 1.6g / cm 3 -1.80g / cm 3 , optional 1.65g / cm 3 -1.75g / cm 3 .

[0008] In any embodiment, the Raman spectrum of the graphite negative electrode active material is 1250 cm -1 Up to 1500cm -1 The peak intensity Id and 1500cm -1 Up to 1650cm -1 The peak intensity Ig ratio Id / Ig is 0.2-0.35.

[0009] In any embodiment, based on the total number of particles of the graphite negative electrode active material, the number of the primary particles in the graphite negative electrode active material accounts for greater than or equal to 85%, and can be optionally 85%-100%.

[0010] The primary particles within the above range are helpful to reduce the structural fragmentation of the graphite negative electrode active material caused by expansion and contraction of the graphite negative electrode active material during the cycle, improve the structural stability of the graphite negative electrode active material, and thus improve the cycle performance of the secondary battery.

[0011] In any embodiment, the graphite negative electrode active material has a graphitization degree of 85%-91%.

[0012] By adjusting the graphitization degree of the graphite negative electrode active material within the above range, the SP 3 There are more bonds, so that the layers of the graphite negative electrode active material are mutually restrained, so that the structure of the graphite negative electrode active material is more stable, and the graphite negative electrode active material has excellent stability during the cycle process, which is conducive to the cycle performance of the graphite negative electrode active material. At the same time, the graphite negative electrode active material has a suitable degree of graphitization, the structure of the graphite negative electrode active material is relatively regular, and the material has a high gram capacity, which can improve the energy density of the battery.

[0013] In any embodiment, the volume distribution particle size Dv50 of the graphite negative electrode active material is less than or equal to 15.0 μm, and can be optionally 9.0 μm-14.0 μm.

[0014] When the volume distribution particle size Dv50 of the graphite negative electrode active material is within an appropriate range, the path of active ion embedding and extraction is reduced, the transmission performance of active ions and electrons is improved, and the rate performance of the battery is improved. In addition, it is also beneficial to reduce the specific surface area of ​​the graphite negative electrode active material, which helps to reduce the irreversible consumption of active ions due to side reactions between the graphite negative electrode active material and the electrolyte during the cycle, thereby improving the cycle performance and storage performance of the secondary battery.

[0015] In any embodiment, the graphite negative electrode active material comprises a core and a coating layer covering at least a surface of the core, the core is artificial graphite, and the coating layer comprises amorphous carbon.

[0016] The "core" of the graphite negative electrode active material is artificial graphite, which reduces the volume change rate during lithium ion deintercalation and reduction of side reactions caused by the breakage and reconstruction of the SEI film during the cycle, thereby improving the battery's cycle performance. At the same time, the "shell" is amorphous carbon, which can effectively reduce the active ion diffusion resistance and particle surface polarization in the material, so that the material's Id / Ig is within a suitable range, which can improve the battery's rate performance.

[0017] In any embodiment, the graphite negative electrode active material satisfies at least one of the following conditions:

[0018] (1) The tap density of the graphite negative electrode active material is 1.0 g / cm 3 -1.4g / cm 3 ;

[0019] (2) The specific surface area of ​​the graphite negative electrode active material is 0.75 m 2 / g-1.75m 2 / g;

[0020] (3) The particle size distribution of the graphite negative electrode active material (Dv90-Dv10) / Dv50 is 1.30-1.80.

[0021] (4) The gram capacity of the graphite negative electrode active material is 325 mAh / g-340 mAh / g.

[0022] By regulating the tap density of the graphite negative electrode active material within the above range, the electron conduction between particles can be further improved, the battery rate performance can be improved, and at the same time it is beneficial to improve the stability of the negative electrode slurry, which is beneficial to the coating of the negative electrode slurry, thereby reducing the processing difficulty, improving the appearance of the negative electrode sheet, and improving the electrical performance of the battery.

[0023] When the specific surface area of ​​the graphite negative electrode active material is within an appropriate range, the negative impact of the side reaction between the graphite negative electrode active material and the electrolyte on the cycle performance can be reduced, thereby improving the cycle performance of the battery.

[0024] Regulating the volume particle size distribution in the graphite negative electrode active material within a suitable range is beneficial for the negative electrode film layer to have a suitable pore structure, thereby reducing the difficulty of ion liquid phase transmission and improving the rate performance of the secondary battery; in addition, the graphite negative electrode active material can also have good particle stacking properties, which is beneficial to improving the compaction density of the negative electrode film layer, thereby further improving the energy density of the secondary battery.

[0025] The gram capacity of the graphite negative electrode active material is within the above range, the lattice expansion of the material during the cycle is relatively small, the crystal structure stability is good, and the irreversible consumption of active ions is reduced, thereby improving the cycle performance of the secondary battery.

[0026] The second aspect of the present application also provides a method for preparing a graphite negative electrode active material, comprising the following steps:

[0027] Provide raw materials;

[0028] Processing the raw material to obtain a precursor;

[0029] The precursor is graphitized to obtain a graphitized product;

[0030] The graphitized product is subjected to surface treatment to obtain a graphite negative electrode active material.

[0031] The powder compaction density of the graphite negative electrode active material under a pressure of 49000N is greater than or equal to 1.60g / cm 3 ;

[0032] In the Raman spectrum of the graphite negative electrode active material, 1250 cm -1 Up to 1500cm -1 The peak intensity Id and 1500cm -1 Up to 1650cm -1 The peak intensity Ig ratio Id / Ig is greater than or equal to 0.15.

[0033] The graphite negative electrode active material prepared by the method has a relatively high powder compaction density and Id / Ig, and can take into account both the energy density and the charge and discharge capacity of the battery. The secondary battery prepared using the material takes into account both high energy density and excellent rate performance.

[0034] In any embodiment, the graphitized product is subjected to a fusion treatment to obtain an intermediate, wherein the frequency of the fusion treatment is 20-40 Hz, and / or the time of the fusion treatment is 5-15 min;

[0035] The intermediate is mixed with asphalt at room temperature and then carbonized to obtain a graphite negative electrode active material.

[0036] In this application, the graphitized product is first subjected to a fusion treatment and then to an asphalt coating treatment. The fusion treatment can achieve the purpose of spheroidization and de-edge. On the one hand, the intermediate obtained by fusion spheroidization has a relatively regular structure, which can improve the powder compaction density of the intermediate. On the other hand, the small particles of graphite produced by de-edge can be filled in the gaps of the intermediate material, further improving the intermediate powder compaction density, and providing a basis for obtaining graphite negative electrode active materials with high powder compaction density.

[0037] In any embodiment, the mass ratio of the intermediate to asphalt is 1:99-10:90, and can be optionally 2:98-5:95.

[0038] When the mass ratio of the intermediate to the asphalt is within a suitable range, the purpose of coating modification can be achieved, so that the graphite negative electrode active material has amorphous carbon of suitable thickness, and the graphite negative electrode active material has a high Id / Ig value, while avoiding excessive negative effects of excessive amorphous carbon on the powder compaction density of the material, so that the material has both high energy density and excellent kinetic properties.

[0039] In any embodiment, the raw material comprises one or more of petroleum coke, needle coke, and pitch coke, and petroleum coke may be selected.

[0040] Based on the total volume of the raw material structure, the volume proportion of the mosaic structure and the regional structure is greater than or equal to 60%, and can be optionally 65%-80%.

[0041] Controlling the volume proportion of the mosaic structure and the regional structure within an appropriate range, the raw materials with better isotropy provide the raw material basis for obtaining graphite negative electrode active materials with high isotropy. During the battery charging and discharging process, the graphite negative electrode active materials can embed active ions in multiple directions, the force is more uniform, and the expansion is relatively small, which is conducive to improving the cycle life of the battery. At the same time, the graphite negative electrode active materials with high isotropy have more active ion transmission channels and short transmission paths, which is conducive to improving the rate performance.

[0042] In any embodiment, the maximum power of the graphitization process is 70%-90% of the rated power of the graphitization process equipment.

[0043] In any embodiment, the maximum power of the graphitization treatment is 21000W-26000W; and / or the constant power time of the graphitization treatment at the maximum power is 8h-40h.

[0044] The maximum power of the appropriate graphitization treatment and / or the constant power time at the maximum power, the powder compaction density and defectivity of the graphitized product are within a suitable range, and after the graphitized product is surface treated, a graphite negative electrode active material with excellent high powder compaction density and defectivity can be obtained.

[0045] In any embodiment, the gram capacity of the graphitized product is 325-340 mAh / g.

[0046] The gram capacity of the graphitized product is within a suitable range, and the powder compaction density and defect degree of the graphitized product are within a suitable range. After the graphitized product is surface treated, a graphite negative electrode active material with relatively high powder compaction density and high defect degree can be obtained.

[0047] In any embodiment, the processing of raw materials specifically comprises the following steps:

[0048] The raw materials are crushed, shaped, and graded, and fine powder after crushing is removed to obtain secondary raw materials;

[0049] Carbonizing the secondary raw material to obtain a precursor,

[0050] Wherein, the volume distribution particle size Dv50 of the secondary raw material is 8.0-16.0 μm, and / or the particle size distribution (Dv90-Dv10) / Dv50 of the secondary raw material is 1.30-1.70.

[0051] Controlling the Dv50 of secondary raw materials within a suitable range is beneficial to controlling the Dv50 of graphite negative electrode active materials within a suitable range, reducing the paths of active ion embedding and extraction, improving the transmission performance of active ions and electrons, improving the rate performance of the battery, and helping to reduce the side reactions of graphite negative electrode active materials and the irreversible consumption of active ions during the cycle process, thereby improving the cycle performance and storage performance of secondary batteries.

[0052] Controlling the particle size distribution (Dv90-Dv10) / Dv50 of the secondary raw materials within a suitable range is beneficial to controlling the particle size distribution (Dv90-Dv10) / Dv50 of the graphite negative electrode active material within a suitable range, which is beneficial for the negative electrode film layer to have a suitable pore structure, thereby reducing the difficulty of ion liquid phase transmission and improving the rate performance of the secondary battery; in addition, the graphite negative electrode active material can also have good particle stacking properties, which is beneficial to improving the compaction density of the negative electrode film layer, thereby further improving the energy density of the secondary battery.

[0053] The third aspect of the present application provides a secondary battery, comprising a negative electrode plate, wherein the negative electrode plate is the graphite negative electrode active material of the first aspect of the present application or the graphite negative electrode active material prepared by the preparation method of the second aspect.

[0054] The fourth aspect of the present application provides an electrical device, comprising the secondary battery described in the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 is a schematic diagram of a secondary battery according to one embodiment of the present application.

[0056] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0057] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.

[0058] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0059] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0060] Figure 6 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0061] Description of reference numerals:

[0062] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION

[0063] Hereinafter, the embodiments of the graphite negative electrode active material and its preparation method, the secondary battery containing the same, and the electric device of the present application are specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0064] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0065] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0066] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0067] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0068] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0069] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0070] Graphite negative electrode active material is one of the important raw materials for negative electrode sheets, and has a great influence on the electrical properties of negative electrode sheets and secondary batteries. In the prior art, in order to improve the rate performance of graphite negative electrode active materials, the graphite negative electrode active materials are mixed evenly with a coating agent (such as asphalt, polymer compounds, etc.) and then heat treated to coat an amorphous carbon layer on the surface of the graphite negative electrode active materials. However, the traditional coating treatment will cause the powder compaction density of the graphite negative electrode active material to be greatly reduced, which affects the compaction density of the negative electrode film layer and reduces the energy density of the secondary battery. It is difficult for the prior art to achieve a perfect balance between high energy density and excellent rate performance.

[0071] [Graphite negative electrode active material]

[0072] The present application provides a graphite negative electrode active material, wherein the powder compaction density of the graphite negative electrode active material under a pressure of 49000N is greater than or equal to 1.60g / cm 3 , 1250cm in the Raman spectrum of graphite negative electrode active materials -1 Up to 1500cm -1 The peak intensity Id and 1500cm -1Up to 1650cm -1 The peak intensity Ig ratio Id / Ig is greater than or equal to 0.15.

[0073] In some embodiments, the powder compaction density of the graphite negative electrode active material under a pressure of 49000N may be 1.60 g / cm 3 , 1.61g / cm 3 、1.62g / cm 3 、1.63g / cm 3 , 1.64g / cm 3 , 1.65g / cm 3 , 1.66g / cm3, 1.67g / cm 3 、1.68g / cm 3 , 1.69g / cm 3 , 1.70g / cm 3 , 1.71g / cm 3 , 1.72g / cm 3 、1.73g / cm 3 , 1.74g / cm 3 , 1.75g / cm 3 , 1.76g / cm 3 , 1.77g / cm 3 , 1.78g / cm 3 , 1.79g / cm 3 , 1.80g / cm 3 、1.81g / cm 3 , 1.82g / cm 3 , 1.83g / cm 3 , 1.84g / cm 3 , 1.85g / cm 3 , or a range between any two of the above values.

[0074] In this article, the term "powder compaction density" refers to the density of the powder to be tested under a preset pressure. The greater the powder compaction density, the higher the mass of the powder material per unit volume. For graphite negative electrode active materials, the higher the powder compaction density, the greater the compaction density of the negative electrode film layer, which is more conducive to increasing the energy density of the secondary battery.

[0075] The graphite negative electrode active material of the present application has a high powder compaction density, and the negative electrode film layer has a high compaction density, providing a material basis for preparing high energy density batteries.

[0076] The method for measuring the compacted density of the powder can be any method known in the art. For example, referring to GB / T24533-2009, 1g of graphite negative electrode active material powder is weighed and added to a bottom area of ​​1.327cm2 The mold is pressurized to a specific pressure, such as 49000N, and the pressure is maintained for 30 seconds, then the pressure is released and maintained for 10 seconds. The powder compaction density of the graphite negative electrode active material under the selected pressure is measured by an electronic pressure testing machine (such as UTM7305 electronic pressure testing machine).

[0077] The Raman spectrum of graphite anode active material is 1250 cm -1 Up to 1500cm -1 The peak intensity Id and 1500cm -1 Up to 1650cm -1 The peak intensity Ig ratio Id / Ig can characterize the ratio of surface defects and crystalline regions of graphite negative electrode active materials. The larger the Id / Ig, the larger the proportion of surface defects in graphite negative electrode active materials. High defectivity can increase the deintercalation channel of active ions and increase the deintercalation speed of active ions, thereby improving the rate performance of graphite negative electrode active materials. The graphite negative electrode active material of the present application has a high Id / Ig ratio, and the high surface defectivity of the graphite negative electrode active material can effectively improve the rate performance of the battery.

[0078] In some embodiments, the Raman spectrum of the graphite negative electrode active material is 1250 cm -1 Up to 1500cm -1 The peak intensity Id and 1500cm -1 Up to 1650cm -1 The peak intensity Ig ratio Id / Ig can be selected as 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.30, 0.35, 0.40, 0.45 or 0.50, or a range between any two of the above values.

[0079] The Raman spectrum of graphite anode active material is 1250 cm -1 Up to 1500cm -1 The peak intensity Id and 1500cm -1 Up to 1650cm -1 The peak intensity Ig ratio Id / Ig can be measured by any method known in the art. For example, an InVia Qontor (Reflex) laser micro-Raman spectrometer is used for testing, wherein a solid laser with a wavelength of 523 nm is used as a light source, 100 points are sampled in a 100 μm×100 μm area, and the peak intensity Ig ratio Id / Ig of each point is calculated. -1 Up to 1500cm -1 The peak intensity Id and 1500cm -1 Up to 1650cm -1The ratio of Id / Ig to the peak intensity Ig was calculated by taking the median of the Id / Ig values ​​of 100 points as the peak intensity at 1250cm in the Raman spectrum of the graphite negative electrode active material. -1 Up to 1500cm -1 The peak intensity Id and 1500cm -1 Up to 1650cm -1 The peak intensity Ig ratio is Id / Ig.

[0080] In summary, the graphite negative electrode active material of the present application has both high powder compaction density and Id / Ig, and the secondary battery prepared using the graphite negative electrode active material can have both energy density and rate performance.

[0081] In some embodiments, the powder compaction density of the graphite negative electrode active material under a pressure of 49000N is 1.60g / cm 3 -1.80g / cm 3 .

[0082] In some embodiments, the powder compaction density of the graphite negative electrode active material under a pressure of 49000N may be 1.60 g / cm 3 , 1.65g / cm 3 , 1.66g / cm 3 , 1.67g / cm 3 、1.68g / cm 3 , 1.69g / cm 3 , 1.70g / cm 3 , 1.71g / cm 3 , 1.72g / cm 3 、1.73g / cm 3 , 1.74g / cm 3 , 1.75g / cm 3 , 1.76g / cm 3 , 1.77g / cm 3 , 1.78g / cm 3 , 1.79g / cm 3 or 1.80g / cm 3 , or a range between any two of the above values.

[0083] In some embodiments, the powder compaction density of the graphite negative electrode active material under a pressure of 49000N is 1.65g / cm 3 -1.75g / cm 3 .

[0084] In some embodiments, the powder compaction density of the graphite negative electrode active material under a pressure of 49000N may be 1.65 g / cm 3 , 1.66g / cm3 , 1.67g / cm 3 、1.68g / cm 3 , 1.69g / cm 3 , 1.70g / cm 3 , 1.71g / cm 3 , 1.72g / cm 3 、1.73g / cm 3 , 1.74g / cm 3 or 1.75g / cm 3 , or a range between any two of the above values.

[0085] By controlling the powder compaction density of the graphite negative electrode active material under a pressure of 49000N within an appropriate range, the negative electrode film layer has a high compaction density, which can improve the energy density of the secondary battery. It is also beneficial for the negative electrode film layer to have a suitable pore structure, reduce the difficulty of ion liquid phase transmission, improve the ion and electron transmission performance, and improve the wetting and retention characteristics of the negative electrode film layer to the electrolyte, thereby further improving the rate performance and cycle performance of the secondary battery.

[0086] In some embodiments, the Raman spectrum of the graphite negative electrode active material is 1250 cm -1 Up to 1500cm -1 The peak intensity Id and 1500cm -1 Up to 1650cm -1 The peak intensity Ig ratio Id / Ig is 0.2-0.35.

[0087] In some embodiments, Id / Ig is 0.2-0.35. In some embodiments, Id / Ig can be 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.30 or 0.35, or a range between any two of the above values.

[0088] If Id / Ig is too large and there are too many defects on the graphite surface, it will affect the thickness of the solid electrolyte interface (SEI) film formed during the first cycle of the secondary battery, resulting in irreversible capacity loss and affecting the energy density and cycle performance of the battery.

[0089] When Id / Ig is within the above range, the surface of the negative electrode material has an appropriate number of defects, which can promote ion adsorption and binding, while reducing the irreversible capacity loss caused by high defect levels, so that the negative electrode film layer has high compaction and can also improve the cycle performance of the battery.

[0090] In some embodiments, based on the total number of particles of the graphite negative electrode active material, the number of the primary particles accounts for greater than or equal to 85%.

[0091] In some embodiments, based on the total number of particles of the graphite negative electrode active material, the number of primary particles accounts for 85%-100%. In some embodiments, based on the total number of primary particles and secondary particles, the number of primary particles can be 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or 100%, or a range between any two of the above values.

[0092] Herein, primary particles have a meaning known in the art. "Primary particles" are also called single particles, and generally refer to non-agglomerated particles. Primary particles can be confirmed by using a scanning electron microscope (SEM) image.

[0093] The number ratio of primary particles can be determined by instruments and methods known in the art. An example is as follows: lay and stick the graphite negative electrode active material on the conductive glue to make a sample to be tested with a length × width = 6 cm × 1.1 cm. Use a scanning electron microscope; an energy spectrometer (such as ZEISS SEM (sigma300)) to test the morphology of the particles in the sample to be tested. The test can refer to JY / T010-1996. In order to ensure the accuracy of the test results, multiple (for example, 10 or 20) different areas can be randomly selected from the sample to be tested for scanning testing, and at a certain magnification (for example, 500 times or 1000 times), the number of primary particles and the total number of particles in the test area are counted. The ratio of the number of primary particles to the total number of particles in any test area is the number ratio of primary particles in the area, and the average value of the test results of 10 test areas is taken as the number ratio of primary particles. In order to ensure the accuracy of the results, multiple samples to be tested (for example, 5 or 10) may be prepared to repeat the above test, and the average value of the test results of each sample to be tested is taken as the percentage of the number of primary particles.

[0094] During the cycle, the graphite negative electrode active material undergoes repeated expansion and contraction deformation, which causes the graphite negative electrode active material particles to break, reducing the mechanical integrity of the graphite negative electrode active material particles; at the same time, the broken particles increase the electrolyte penetration and side reaction degree, increase the irreversible consumption of active ions, and have a negative impact on the battery's cycle performance. The primary particles have excellent structural stability, which helps to reduce the graphite negative electrode active material particle breakage caused by expansion and contraction during the cycle, improve the chemical mechanical stability of the graphite negative electrode active material, reduce the irreversible consumption of active ions, and achieve the improvement of the secondary battery cycle performance.

[0095] In some embodiments, the graphite negative electrode active material has a graphitization degree of 85%-91%. In some embodiments, the graphitization degree of the graphite negative electrode active material can be 85%, 86%, 87%, 88%, 89%, 90% or 91%, or a range between any two of the above values.

[0096] In the present application, the graphitization degree of the graphite negative electrode active material is a well-known meaning in the art, and can be tested using instruments and methods known in the art. For example, an X-ray diffractometer (such as Bruker D8 Discover) can be used for testing, and the test can refer to JISK 0131-1996 and JB / T 4220-2011 to obtain the average interlayer spacing d002 of the C(002) crystal plane in the material crystal structure, and then the graphitization degree is calculated according to the formula g=(0.344-d002) / (0.344-0.3354)×100%. In the above formula, d002 is the average interlayer spacing of the C(002) crystal plane in the material crystal structure expressed in nanometers (nm).

[0097] The degree of graphitization reflects the completeness of the graphite crystal structure in the material, that is, the regularity of the arrangement of carbon atoms in the graphite structure of the material. A material with a high degree of graphitization indicates that the distance between graphite layers is small, the smaller the lattice rotation, the less scattered stacking of the layers, the more orderly the arrangement, and the higher the specific capacity of the material. A material with a low degree of graphitization indicates that the distance between graphite layers is large, which is conducive to the rapid deintercalation of active ions and the improvement of the battery's rate performance. The large distance between graphite layers means that the material expands less when lithium is inserted, which has the effect of shallow charge and shallow discharge. At the same time, the material has a low degree of graphitization, and the SP in the graphite negative electrode active material is high. 3 The more bonds, the layers of the graphite negative electrode active material are restrained from each other, making the structure of the graphite negative electrode active material more stable. The graphite negative electrode active material has excellent stability during the cycle and is conducive to long-term circulation.

[0098] By regulating the graphitization degree of the graphite negative electrode active material within the above range, the material's cycle stability, gram capacity and active ion transport performance can be taken into account, which is conducive to obtaining a battery with high energy density, long cycle and high rate performance.

[0099] In some embodiments, the volume distribution particle size Dv50 of the graphite negative electrode active material is less than or equal to 15.0 μm.

[0100] In some embodiments, the volume distribution particle size Dv50 of the graphite negative electrode active material can be selected to be less than or equal to 15.0 μm, less than or equal to 14.0 μm, less than or equal to 13.0 μm, less than or equal to 12.0 μm, less than or equal to 11.0 μm, less than or equal to 10.0 μm or less than or equal to 9.0 μm.

[0101] In this application, the volume distribution particle size Dv50 of the carbon-based negative electrode material has a well-known meaning in the art, which respectively represents the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%, and can be measured using instruments and methods known in the art. For example, it can be measured with a laser particle size analyzer with reference to GB / T19077-2016. The test instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0102] Graphite negative electrode active materials have a small volume distribution particle size Dv50, and the path for active ion embedding and extraction is short, which can improve the transmission performance of active ions and electrons and improve the rate performance of the material.

[0103] In some embodiments, the volume distribution particle size Dv50 of the graphite negative electrode active material is 9.0 μm-14.0 μm.

[0104] In some embodiments, the volume distribution particle size Dv50 of the graphite negative electrode active material can be selected as 9.0 μm, 9.5 μm, 10.0 μm, 10.5 μm, 11.0 μm, 11.5 μm, 12.0 μm, 12.5 μm, 13.0 μm, 13.5 μm, 14.0 μm or a range between any two of the above values.

[0105] When the volume distribution particle size Dv50 of the graphite negative electrode active material is within an appropriate range, the path of active ion embedding and extraction is reduced, the transmission performance of active ions and electrons is improved, and the rate performance of the battery is improved. In addition, it is also beneficial to reduce the specific surface area of ​​the graphite negative electrode active material, which helps to reduce the side reactions of the graphite negative electrode active material and the irreversible consumption of active ions during the cycle process, thereby improving the cycle performance and storage performance of the secondary battery.

[0106] In some embodiments, the graphite negative electrode active material comprises a core and a coating layer covering at least a surface of the core, the core is artificial graphite, and the coating layer comprises amorphous carbon.

[0107] In this article, the term "artificial graphite" refers to carbon materials obtained by high-temperature graphitization.

[0108] As used herein, the term "amorphous carbon" refers to a carbon material with a low degree of graphitization and crystallization and a disordered and irregular microstructure.

[0109] The "core" of the graphite negative electrode active material is artificial graphite, which reduces the volume change rate during lithium ion deintercalation and reduction of side reactions caused by the breakage and reconstruction of the SEI film during the cycle, thereby improving the battery's cycle performance. At the same time, the "shell" is amorphous carbon, which can effectively reduce the active ion diffusion resistance and particle surface polarization in the material, so that the material's Id / Ig is within a suitable range, which can improve the battery's rate performance.

[0110] In some embodiments, the tap density of the graphite negative electrode active material is 1.0 g / cm 3 -1.4g / cm 3 In some embodiments, the tap density of the graphite negative electrode active material may be 1.0 g / cm 3 , 1.05g / cm 3 , 1.1g / cm 3 , 1.15g / cm 3 , 1.20g / cm 3 , 1.25g / cm 3 , 1.3g / cm 3 or 1.4g / cm 3 , or a range between any two of the above values.

[0111] In this article, the term "tap density" refers to the density of a powder material after vibration compression under certain conditions.

[0112] The tap density of the graphite negative electrode active material can be measured using instruments and methods known in the art. For example, it can be measured using a powder tap density tester in accordance with GB / T 5162-2006. The test instrument can be Dandong Better BT-301. The test parameters are as follows: vibration frequency 250±15 times / min, amplitude 3±0.2 mm, vibration number 5000 times, and measuring cylinder 25 mL.

[0113] By regulating the tap density of the graphite negative electrode active material within the above range, the electron conduction between particles can be further improved, the battery rate performance can be improved, and at the same time it is beneficial to improve the stability of the negative electrode slurry, which is beneficial to the coating of the negative electrode slurry, thereby reducing the processing difficulty, improving the appearance of the negative electrode sheet, and improving the electrical performance of the battery.

[0114] In some embodiments, the specific surface area of ​​the graphite negative electrode active material is 0.75 m 2 / g-1.75m 2 In some embodiments, the specific surface area of ​​the graphite negative electrode active material can be 0.75 m 2 / g, 0.85m 2 / g, 0.95m 2 / g, 1.05m 2 / g, 1.15m 2 / g, 1.25m 2 / g, 1.35m 2 / g, 1.45m 2 / g, 1.55m 2 / g, 1.65m 2 / g or 1.75m 2 / g, or the range between any two of the above values.

[0115] The specific surface area of ​​the graphite negative electrode active material is a well-known meaning in the art and can be measured by instruments and methods well-known in the art. For example, it can be measured by nitrogen adsorption specific surface area analysis test method according to GB / T 19587-2017 and calculated by BET (Brunauer Emmett Teller) method, wherein the nitrogen adsorption specific surface area analysis test can be performed by Tri-Star 3020 specific surface area pore size analysis tester of Micromeritics, USA.

[0116] The specific surface area of ​​the graphite negative electrode active material is within an appropriate range, and the material has appropriate adsorption sites, which can promote the adsorption of active ions and improve the rate performance of the secondary battery. At the same time, it can avoid excessive side reactions between the graphite negative electrode active material and the electrolyte, which will have a negative impact on the cycle performance, and take into account both the cycle performance and rate performance of the battery.

[0117] In some embodiments, the volume particle size distribution (Dv90-Dv10) / Dv50 of the graphite negative electrode active material is 1.30-1.80. In some embodiments, the volume particle size distribution (Dv90-Dv10) / Dv50 of the graphite negative electrode active material can be selected as 1.30, 1.35, 1.40, 1.45, 1.50, 1.60, 1.70 or 1.80, or a range between any two of the above values.

[0118] The volume distribution particle sizes Dv10, Dv50, and Dv90 of the graphite negative electrode active material are well known in the art, and respectively represent the particle sizes corresponding to the cumulative volume distribution percentages of the material reaching 10%, 50%, and 90%, and can be measured using instruments and methods known in the art. For example, the particle size distribution laser diffraction method according to GB / T 19077-2016 can be referred to, and a Malvern laser particle size analyzer can be used for characterization testing, such as the Mastersizer-3000 of Malvern for testing.

[0119] Regulating the volume particle size distribution in the graphite negative electrode active material within a suitable range is beneficial for the negative electrode film layer to have a suitable pore structure, thereby reducing the difficulty of ion liquid phase transmission and improving the rate performance of the secondary battery; in addition, the graphite negative electrode active material can also have good particle stacking properties, which is beneficial to improving the compaction density of the negative electrode film layer, thereby further improving the energy density of the secondary battery.

[0120] In some embodiments, the gram capacity of the graphite negative electrode active material is 325 mAh / g-340 mAh / g.

[0121] Herein, the term "gram capacity" refers to the ratio of the capacity that can be released by the graphite negative electrode active material to the mass of the graphite negative electrode active material. Generally speaking, the higher the gram capacity, the more conducive it is to improving the energy density of the secondary battery.

[0122] In some embodiments, the gram capacity of the graphite negative electrode active material is 325mAh / g, 328mAh / g, 329mAh / g, 330mAh / g, 331mAh / g, 332mAh / g, 333mAh / g, 334mAh / g, 335mAh / g, 336mAh / g, 337mAh / g or 340mAh / g, or a range between any two of the above values.

[0123] The gram capacity can be measured by any known method in the art. For example, the graphite negative electrode active material sample can be mixed with the conductive agent carbon black and polyvinylidene fluoride (PVDF) in a mass ratio of 91.6:1.8:6.6 in an appropriate amount of solvent NMP to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the surface of the negative electrode current collector copper foil and dried and cold pressed; then the metal lithium sheet is used as the counter electrode and the polypropylene (PP) film is used as the isolation membrane, and the electrolyte is injected, wherein the electrolyte formula used is as follows: dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) are mixed in a weight ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L. CR2430 button cells are assembled in an argon-protected glove box. At 25°C, the button cell prepared above was first discharged at a constant current of 0.05C to 0.005V, then discharged at a constant current of 10μA to 0.005V, and left to stand for 5 minutes, and the first cycle discharge capacity of the button cell was recorded; then, the button cell was charged at a constant current of 0.1C to 2.0V, and the charging capacity of the button cell was recorded. The ratio of the charging capacity of the button cell to the mass of the graphite negative electrode active material sample is the gram capacity of the graphite negative electrode active material.

[0124] The gram capacity of the graphite negative electrode active material is within the range, the lattice expansion during the material cycle is relatively small, the crystal structure stability is good, the irreversible consumption of active ions is reduced, and the battery cycle performance is improved; at the same time, the graphite negative electrode active material has excellent capacitance and can improve the energy density of the secondary battery.

[0125] [Method for preparing graphite negative electrode active material]

[0126] The present application also provides a method for preparing a graphite negative electrode active material, comprising the following steps:

[0127] Provide raw materials;

[0128] Processing the raw material to obtain a precursor;

[0129] The precursor is graphitized to obtain a graphitized product;

[0130] The graphitized product is subjected to surface treatment to obtain a graphite negative electrode active material.

[0131] The powder compaction density of the graphite negative electrode active material under a pressure of 49000N is greater than or equal to 1.60g / cm 3 ;

[0132] In the Raman spectrum of the graphite negative electrode active material, 1250 cm -1 Up to 1500cm -1 The peak intensity Id and 1500cm -1 Up to 1650cm -1 The peak intensity Ig ratio Id / Ig is greater than or equal to 0.15.

[0133] The graphite negative electrode active material prepared by the method has high energy density and excellent charge and discharge capacity, and the secondary battery prepared by using the material has both high energy density and excellent rate performance.

[0134] In some embodiments, the surface treatment is to perform a fusion treatment on the graphitized product to obtain an intermediate, wherein the frequency of the fusion treatment is 20-40 Hz, and / or the time of the fusion treatment is 5-15 min;

[0135] The intermediate is mixed with asphalt at room temperature and then carbonized to obtain a graphite negative electrode active material.

[0136] The existing technology directly uses asphalt to coat the graphitized product to improve the surface defect degree of the graphite negative electrode active material, thereby improving the rate performance of the material. However, directly coating the graphitized product will seriously affect the material powder compaction density, reduce the compaction density of the negative electrode film layer, and thus affect the energy density of the secondary battery.

[0137] The present application performs a fusion treatment on the graphitized product under specific process conditions before the asphalt coating treatment, which can achieve the purpose of spheroidization and de-edgeing. On the one hand, the intermediate obtained by fusion spheroidization has a relatively regular structure, which can improve the powder compaction density of the intermediate. On the other hand, the small particles of graphite produced by de-edgeing can be filled in the gaps of the intermediate material, further improving the powder compaction density of the intermediate. The fusion treatment can effectively compensate for the adverse effects of the asphalt coating treatment on the powder compaction density of the material, which is conducive to obtaining a negative electrode film layer with a high compaction density, and is conducive to obtaining a graphite negative electrode active material with high energy density and excellent rate performance.

[0138] In some embodiments, the frequency of the fusion process may be selected to be 20 Hz, 25 Hz, 30 Hz, 35 Hz or 40 Hz, or a range between any two of the above values.

[0139] The frequency of fusion treatment affects the powder compaction density and specific surface area of ​​graphite negative electrode active materials. A high frequency of fusion treatment can increase the powder compaction density of graphite negative electrode active materials, while also avoiding damage to processing equipment caused by excessively high frequency of fusion treatment.

[0140] In some embodiments, the fusion treatment time is 5-15 min. In some embodiments, the fusion treatment time can be selected as 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min or 15 min, or a range between any two of the above values.

[0141] The time of fusion treatment affects the powder compaction density, specific surface area and Id / Ig of graphite negative electrode active materials. Long fusion treatment time can increase the powder compaction density and Id / Ig of graphite negative electrode active materials, obtain a negative electrode film layer with high compaction density, and improve the energy density of the battery.

[0142] In some embodiments, the carbonization treatment is performed at a temperature of 950°C to 1350°C.

[0143] In some embodiments, the treatment temperature of the carbonization treatment may be 950° C., 1000° C., 1100° C., 1200° C., 1300° C. or 1350° C., or a range between any two of the above values.

[0144] The treatment temperature of the carbonization treatment affects the Id / Ig of the graphite negative electrode active material. If the treatment temperature of the carbonization treatment is too high, the asphalt coating degree is high, the coating layer of the graphite negative electrode active material is highly complete, and the Id / Ig of the graphite negative electrode active material is reduced, which is not conducive to improving the rate performance of the battery. If the treatment temperature of the carbonization treatment is too low, the surface functional groups of the asphalt may not be completely removed, which will cause side reactions during the cycle process and affect the cycle performance of the battery.

[0145] In some embodiments, the feedstock comprises one or more of petroleum coke, needle coke, and pitch coke.

[0146] As used herein, the term "petroleum coke" refers to coke formed by high-temperature carbonization of petroleum residue or petroleum asphalt.

[0147] As used herein, the term "needle coke" refers to coal tar pitch or petroleum pitch, which, after undergoing liquid phase carbonization to generate an anisotropic mesophase, can generate coke with a needle-like texture after undergoing processes such as high-temperature carbonization.

[0148] As used herein, the term "pitch coke" refers to a solid material produced by carbonizing coal tar pitch at high temperatures.

[0149] In some embodiments, the feedstock comprises petroleum coke.

[0150] Petroleum coke has excellent anisotropy, which is beneficial for preparing low-graphitization, low-expansion graphite negative electrode active materials, and is beneficial for long cycle life of batteries. In addition, petroleum coke has a wider source, which is conducive to industrial production.

[0151] The above-mentioned raw materials usually include at least one of mosaic, regional and fiber structures. Usually, based on the morphological characteristics and isochromatic zone size of the coke material under a polarizing microscope, isochromatic zone microstructures with a size less than 30 μm are judged as mosaic, isochromatic zone microstructures with a size greater than 30 μm are judged as regional, and anisotropic strip-shaped isochromatic zones are judged as fiber structures.

[0152] In some embodiments of the present application, based on the total volume of the raw material structure, the volume proportion of the mosaic and regional structures in the raw material is greater than or equal to 60%, and can be optionally 65%-80%.

[0153] In some embodiments, based on the total volume of the raw material structure, the volume proportion of the mosaic structure and the regional structure can be selected to be 60%, 65%, 70%, 75%, 80%, 85% or 90%, or a range between any two of the above values.

[0154] In this application, the volume proportion of mosaic and regional structures in the raw material can be tested by methods known in the art. As an example, take the raw material according to GB 1997-89, mix the raw material crushed to 1mm, shrink it to 40g~50g, use a square hole sieve to take 0.07mm~1.0mm grade sample 4g~5g for film making; prepare powder coke and block coke light film according to MT 116.1-86, the diameter of the powder coke light film shall not be less than 22mm, and the volume occupied by the cement shall be less than 1 / 3; place the sample on a slide with cement, flatten it, and place it on the stage to align the focus, calibrate the microscope, and adjust the polarizer and analyzer to make them orthogonal. Insert the azurite inspection plate (1λ) to make the field of view present the interference color of primary red; determine the step length of the moving ruler to ensure that more than 400 effective measuring points are evenly distributed, and the point spacing is 0.3~0.5mm and the line spacing is generally 0.5~0.8mm. Starting from one end of the sample, determine the type of microstructure under the intersection of the crosshairs, and divide the number of effective measuring points of the mosaic-type and regional-type structure optical tissues by the total number of statistical testing points as the volume proportion of the mosaic-type and regional-type structures in the raw material.

[0155] Raw materials with more mosaic structures and regional structures have excellent isotropy, which is beneficial to reducing the degree of graphitization of graphite negative electrode active materials, making the expansion of graphite negative electrode active materials relatively small during the cycle process, which is beneficial to improving the cycle stability of the material.

[0156] In some embodiments, based on the total volume of the raw material structure, the volume proportion of the mosaic structure and the regional structure can be selected to be 65%, 70%, 75% or 80%, or a range between any two of the above values.

[0157] Too high a volume ratio of the mosaic structure and the regional structure will reduce the powder compaction density of the graphite negative electrode active material and the gram capacity of the graphite negative electrode active material, affecting the energy density of the battery. Controlling the volume ratio of the mosaic structure and the regional structure can take into account both the energy density and the cycle performance of the battery.

[0158] In some embodiments, the maximum power of the graphitization process is 70%-90% of the rated power of the graphitization process equipment.

[0159] In some embodiments, the maximum power of the graphitization treatment can be selected as 70%, 75%, 80%, 85%, 90% or any range of values ​​between the rated power of the graphitization treatment equipment. It can be understood that the graphitization treatment equipment refers to any device capable of graphitization treatment, including but not limited to Acheson furnace, box furnace, inner series furnace, continuous graphitization, electric calcining furnace, medium frequency furnace, tubular furnace and other devices. Among them, the rated power of graphitization treatment equipment produced by different manufacturers may be different, and it can be selected according to the actual situation.

[0160] In some embodiments, the graphitization treatment equipment is an inner series furnace, and the rated power of the inner series furnace is 25000-32000W.

[0161] In some embodiments, the graphitization treatment equipment is an Acheson furnace, and the rated power of the Acheson furnace is 28000-30000W.

[0162] The maximum power of the graphitization treatment used in this application needs to be lower than the rated power of the graphitization treatment equipment to achieve uniformity of the temperature field during the graphitization treatment process, ensure the consistency of the material's gram capacity, and help improve the cycle life of the battery.

[0163] In some embodiments, the maximum power of the graphitization treatment is 21000 W-26000 W. In some embodiments, the maximum power of the graphitization treatment can be selected as 21000 W, 23000 W, 23500 W, 24000 W, 26000 W or any range therebetween.

[0164] In some embodiments, the graphitization treatment is performed at a constant power time of 8 h to 40 h at maximum power.

[0165] In some embodiments, the graphitization treatment is performed at a constant power time of maximum power of 8 h, 13 h, 16 h, 19 h, 22 h, 25 h, 28 h, 31 h, 33 h, 36 h, 39 h, 40 h, or any range therebetween.

[0166] In some embodiments, the graphitization treatment equipment is an inner series furnace, and the graphitization treatment is performed at a constant power time of 8h-20h at maximum power, and can be optionally 9h-16h. For example, the graphitization treatment can be performed at a constant power time of 8h, 15h, 20h, or any range therebetween.

[0167] In some embodiments, the graphitization treatment equipment is an Acheson furnace, and the graphitization treatment is carried out at a constant power time of 20 hours to 40 hours at maximum power. For example, the graphitization treatment is carried out at a constant power time of 20 hours, 30 hours, 35 hours, 40 hours, or any range of values ​​therebetween.

[0168] The maximum power of the appropriate graphitization treatment and / or the constant power time at the maximum power, the powder compaction density and defectivity of the graphitized product are within a suitable range, and after the graphitized product is surface treated, a graphite negative electrode active material with excellent powder compaction density and defectivity can be obtained.

[0169] In some embodiments, the gram capacity of the graphitized product is 325-340 mAh / g. In some embodiments, the gram capacity of the graphitized product can be 325 mAh / g, 330 mAh / g, 335 mAh / g or 340 mAh / g, or a range between any two of the above values.

[0170] The gram capacity of the graphitized product is within a suitable range, and the compaction density and defect degree of the graphitized product are within a suitable range. After the graphitized product is surface treated, a graphite negative electrode active material with excellent powder compaction density and defect degree can be obtained.

[0171] In some embodiments, the processing of the raw material specifically comprises the following steps:

[0172] The raw materials are crushed, shaped, and graded, and fine powder after crushing is removed to obtain secondary raw materials;

[0173] Carbonizing the secondary raw material to obtain a precursor,

[0174] Wherein, the volume distribution particle size Dv50 of the secondary raw material is 8.0-16.0 μm, and / or the particle size distribution (Dv90-Dv10) / Dv50 of the secondary raw material is 1.30-1.70.

[0175] In some embodiments, in the step of crushing the raw material, a crusher, such as a jaw crusher, can be used to crush the coke raw material. For example, the raw material can be crushed to a set particle size before screening.

[0176] In some embodiments, in the step of shaping the raw material, a shaping machine can be used to shape the crushed raw material. The shaping process can reduce burrs on the surface of the crushed raw material.

[0177] In some embodiments, in the step of classifying the raw materials, an air flow classifier can be used to classify the shaped raw materials. Optionally, the induced air frequency can be greater than or equal to 20 Hz, and the classification frequency can be greater than or equal to 65 Hz. Classification can reduce the content of large particles and fine powder in the obtained precursor.

[0178] In some embodiments, the volume distribution particle size Dv50 of the secondary raw material can be selected to be 8.0 μm, 9.0 μm, 10.0 μm, 11.0 μm, 12.0 μm, 13.0 μm, 14.0 μm, 15.0 μm or 16.0 μm, or a range between any two of the above values.

[0179] Controlling the Dv50 of secondary raw materials within a suitable range is beneficial to controlling the Dv50 of graphite negative electrode active materials within a suitable range, reducing the paths of active ion embedding and extraction, improving the transmission performance of active ions and electrons, improving the rate performance of the battery, and helping to reduce the side reactions of graphite negative electrode active materials and the irreversible consumption of active ions during the cycle process, thereby improving the cycle performance and storage performance of secondary batteries.

[0180] In some embodiments, the particle size distribution of the secondary raw material (Dv90-Dv10) / Dv50 can be selected as 1.30, 1.40, 1.50, 1.60 or 1.70, or a range between any two of the above values.

[0181] Controlling the particle size distribution (Dv90-Dv10) / Dv50 of the secondary raw materials within a suitable range is beneficial to controlling the particle size distribution (Dv90-Dv10) / Dv50 of the graphite negative electrode active material within a suitable range, which is beneficial for the negative electrode film layer to have a suitable pore structure, thereby reducing the difficulty of ion liquid phase transmission and improving the rate performance of the secondary battery; in addition, the graphite negative electrode active material can also have good particle stacking properties, which is beneficial to improving the compaction density of the negative electrode film layer, thereby further improving the energy density of the secondary battery.

[0182] In addition, the secondary battery, battery module, battery pack, and electric device of the present application will be described below with reference to the drawings as appropriate.

[0183] In one embodiment of the present application, a secondary battery is provided.

[0184] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0185] [Positive electrode]

[0186] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.

[0187] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0188] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0189] In some embodiments, the positive electrode active material may adopt a positive electrode active material for a battery known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxides (such as LiCoO 2 ), lithium nickel oxide (such as LiNiO 2 ), lithium manganese oxide (such as LiMnO 2 、LiMn 2 O 4 ), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (Also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O 2 (Also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O 2 (Also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O 2 (Also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O 2 (Also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi0.85 Co 0.15 Al 0.05 O 2 ) and its modified compounds, etc. Examples of lithium phosphates containing olivine structures may include, but are not limited to, lithium iron phosphate (such as LiFePO 4 (also referred to as LFP), composite materials of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO 4 ), at least one of a composite material of lithium manganese phosphate and carbon, a composite material of lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0190] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0191] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0192] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0193] [Negative electrode]

[0194] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes the graphite negative electrode active material in any embodiment.

[0195] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0196] In some embodiments, the negative electrode film layer may further include other negative electrode active materials in addition to the above-mentioned graphite negative electrode active material. In some embodiments, the other negative electrode active materials include but are not limited to one or more of conventional natural graphite, other artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate. The silicon-based material may include one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite and silicon alloy material. The tin-based material may include one or more of elemental tin, tin oxide and tin alloy material.

[0197] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0198] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0199] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0200] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0201] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as graphite negative electrode active material, conductive agent, binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0202] [Electrolytes]

[0203] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0204] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0205] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0206] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0207] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0208] [Isolation film]

[0209] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0210] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0211] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0212] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0213] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0214] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.

[0215] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0216] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0217] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0218] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0219] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0220] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0221] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited to these.

[0222] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.

[0223] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0224] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0225] Example

[0226] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0227] 1. Preparation method

[0228] Example 1

[0229] (1) Preparation of graphite negative electrode active materials

[0230] The petroleum coke raw material with a volume proportion of 65% of the mosaic and regional structures is coarsely crushed, and then the coarsely crushed material is crushed and sieved, and the sieved material is shaped, graded, and finely powdered to obtain a secondary raw material with a Dv50 particle size of 12.0 μm and a particle size distribution of (Dv90-Dv10) / Dv50 of 1.61;

[0231] The secondary raw materials were placed in a kiln for pre-carbonization at a temperature of 1000°C and a high temperature zone time of 24 hours to obtain a precursor with a tap density of 0.99 g / cm 3 ;

[0232] The precursor is graphitized in an inner series furnace at a graphitization temperature of 2850°C and a maximum power of 25000W (herein, it refers to the actual power used by the inner series furnace, which accounts for about 85% of the rated power of the inner series furnace). After the power is kept constant for 9.5 hours, the surface temperature of the graphite crucible of the inner series furnace is cooled to 300°C to obtain a graphitized product.

[0233] The graphitized product was fused in a high-speed fusion machine to obtain an intermediate, the fusion frequency was 40 Hz, the fusion time was 10 min, the intermediate was mixed with asphalt, wherein the mass ratio of the intermediate to asphalt was 98%:2%, and after mixing, carbonization was carried out at 1150°C, and the carbonization time was 2 h. After the finished product demagnetization and mixed batch process, a graphite negative electrode active material was obtained, and its powder compaction density under a pressure of 49000 N was 1.70 g / cm 3 The ratio of the peak intensity Id from 1250cm-1 to 1500cm-1 to the peak intensity Ig from 1500cm-1 to 1650cm-1 in its Raman spectrum is 0.27, and the degree of graphitization is 89.1%.

[0234] (2) Preparation of secondary batteries

[0235] The prepared negative electrode active material, conductive agent carbon black Super P, thickener sodium carboxymethyl cellulose, and binder styrene butadiene rubber were mixed in a mass ratio of 96:1:1.2:1.8, and deionized water was added as a solvent. The mixture was stirred under the action of a vacuum mixer until the system was uniform to obtain a negative electrode slurry. The negative electrode slurry was evenly coated on the negative electrode current collector copper foil to form a negative electrode film layer, and the negative electrode sheet was obtained after drying, cold pressing, and cutting. The surface density of the negative electrode film layer is 0.99 mg / cm 2 The cold pressing roller gap of the cold pressing treatment is -199, and the cold pressing pressure is 50T.

[0236] 2) Preparation of positive electrode

[0237] The positive electrode active material lithium iron phosphate (LFP), the conductive agent Super P, and the binder polyvinylidene fluoride were mixed in a mass ratio of 97:1:2, and the solvent N-methylpyrrolidone was added. The mixture was stirred under the action of a vacuum mixer until the system was uniform to obtain a positive electrode slurry. The positive electrode slurry was evenly coated on the positive electrode current collector aluminum foil, and the positive electrode sheet was obtained after drying, cold pressing, and cutting. The compaction density of the positive electrode film layer was 2.50 g / cm 3 , surface density is 19.7mg / cm 2 .

[0238] 3) Preparation of electrolyte

[0239] In an argon atmosphere glove box with a water content of less than 10 ppm, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) were mixed in a weight ratio of 1:1:1 to obtain an organic solvent, and then LiPF 6 Dissolve in the above organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L, and then add vinylene carbonate (VC), the content of VC being 2% of the total mass of the electrolyte.

[0240] 5) Isolation film

[0241] Polypropylene film is used as the isolation film.

[0242] 6) Preparation of secondary batteries

[0243] The positive electrode sheet, separator and negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0244] The preparation methods of Examples 2-5 are basically the same as those of Example 1, except that the gram capacity of the graphitized product is adjusted by adjusting the volume ratio of the mosaic structure and the regional structure in the raw material, the maximum power of the graphitization treatment, or the constant power time of the graphitization treatment at the maximum power, as shown in Table 1.

[0245] The preparation method of Example 6 is basically the same as that of Example 1, except that the gram capacity of the graphitized product is adjusted by adjusting the volume proportion of the mosaic structure and the regional structure in the raw material, the maximum power of the graphitization treatment or the constant power time of the graphitization treatment at the maximum power, and the fusion frequency and fusion time of the fusion treatment are adjusted, as shown in Table 1.

[0246] Table 1

[0247]

[0248] The preparation method of Comparative Example 1 is substantially the same as that of Example 1, except that no fusion treatment and no asphalt coating treatment are performed during the preparation of the graphite negative electrode active material.

[0249] The preparation method of Comparative Example 2 is substantially the same as that of Example 2, except that the graphite negative electrode active material is directly coated without being subjected to fusion treatment during its preparation.

[0250] 2. Performance Test

[0251] 1. Cycle performance test of secondary batteries

[0252] At 60°C, the batteries of the above embodiments and comparative examples were charged at a constant current of 1C to a voltage of 3.65V, then charged at a constant voltage of 3.65V to a current ≤ 0.05C, and then discharged at a constant current of 1C to a voltage of 2.5V. This was a charge and discharge process, and the discharge capacity C1 of the first cycle was recorded. The charge and discharge cycles were repeated until the battery capacity decayed to 80% of the initial capacity C1, and the test was stopped, and the number of cycle tests was recorded.

[0253] 2. Charging time of secondary batteries

[0254] At 25°C, the secondary battery was charged to 3.65V at a constant current of 0.33C, then charged to a current of 0.05C at a constant voltage, and after standing for 5 minutes, the secondary battery was discharged to 2.50V at a constant current of 0.33C, and its actual capacity was recorded as C0.

[0255] Then the secondary battery is charged with 1.0C0, 1.3C0, 1.5C0, 1.8C0, 2.0C0, 2.3C0, 2.5C0, 3.0C0, constant current to 3.5V or 0V negative electrode cut-off potential (whichever is reached first), and it needs to be discharged to 2.5V at 1C0 after each charging is completed. The negative electrode potential corresponding to charging to 10%, 20%, 30%, ..., 80% SOC (State of Charge) at different charging rates is recorded, and the charging rate-negative electrode potential curve under different SOC states is drawn. After linear fitting, the charging rate corresponding to the negative electrode potential of 0V under different SOC states is obtained. The charging rate is the charging window under the SOC state, which is recorded as C10%SOC, C20%SOC, C30%SOC, C40%SOC, C50%SOC, C60%SOC, C70%SOC, C80%SOC, C90%SOC, C10%SOC, C110%SOC, C120%SOC, C130%SOC, C140%SOC, C150%SOC, C160%SOC, C170%SOC, C180%SOC, C190%SOC, C200%SOC, C210%SOC, C220%SOC, C230%SOC, C240%SOC, C250%SOC, C260%SOC, C270%SOC, C300%SOC, C310%SOC, C320%SOC, C330%SOC, C340%SOC, C350%SOC, C360%SOC, C370%SOC, C380%SOC, C400%SOC, C410%SOC, C420% 80% SOC, according to the formula (60 / C10% SOC+60 / C20% SOC+60 / C30% SOC+60 / C40% SOC+60 / C50% SOC+60 / C60% SOC+60 / C70% SOC+60 / C80% SOC)×10%, the charging time T of the secondary battery from 10% SOC to 80% SOC (assuming that the secondary battery does not precipitate lithium) is calculated in min. The shorter the charging time, the better the fast charging performance of the secondary battery.

[0256] 3. Compaction density of negative electrode film

[0257] The compaction density of the negative electrode film layer can be tested by methods known in the art. As an example, an electronic balance is used to weigh a negative electrode sheet test sample with an area of ​​S, and the weight is recorded as W1, and a micrometer is used to measure the thickness T1 of the negative electrode sheet. Then the weighed electrode sheet film layer is wiped off, the weight of the negative electrode current collector is weighed, recorded as W2, and the thickness T2 of the negative electrode current collector is measured using a micrometer. Then the compaction density of the negative electrode film layer PD = (W1-W2) / [(T1-T2)×S].

[0258] 3. Results

[0259] As shown in Table 2, the powder compaction density of the graphite negative electrode active material provided in the embodiment of the present application is greater than or equal to 1.60 g / cm 3 , and the Raman spectrum of the graphite negative electrode active material is 1250cm -1 Up to 1500cm -1 The peak intensity Id and 1500cm -1 Up to 1650cm -1The peak intensity Ig ratio Id / Ig is greater than or equal to 0.15. From the comparison between Examples 1-6 and Comparative Examples 1-2, it can be seen that the graphite negative electrode active material of the present application takes into account both high powder compaction density and Id / Ig. On the premise that the negative electrode film layer has a high compaction density, the charging time of the battery from 10% SOC to 80% SOC can be shortened, so that the secondary battery can effectively improve the rate performance of the battery under the premise of having a relatively high energy density, and at the same time, the number of cycles of the battery can be increased, and the cycle performance of the battery can be improved.

[0260] As can be seen from Table 2, the graphitization degree of the graphite negative electrode active material is between 85% and 91%, the negative electrode film layer has a high compaction density, and the battery has a short charging time from 10% SOC to 80% SOC and a large number of cycles, and the secondary battery has a high energy density, excellent cycle performance and rate performance.

[0261] Table 2

[0262]

[0263] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A graphite negative electrode active material, characterized in that: The powder compaction density of the graphite negative electrode active material under a pressure of 49000N is greater than or equal to 1.60g / cm 3 In the Raman spectrum of the graphite negative electrode active material, 1250 cm -1 Up to 1500cm -1 The peak intensity Id and 1500cm -1 Up to 1650cm -1 The peak intensity Ig ratio Id / Ig is greater than or equal to 0.

15.

2. The graphite negative electrode active material according to claim 1, characterized in that: The powder compaction density of the graphite negative electrode active material under a pressure of 49000N is 1.60g / cm 3 -1.80g / cm 3 , optional 1.65g / cm 3 -1.75g / cm 3 .

3. The graphite negative electrode active material according to claim 1 or 2, characterized in that: In the Raman spectrum of the graphite negative electrode active material, 1250 cm -1 Up to 1500cm -1 The peak intensity Id and 1500cm -1 Up to 1650cm -1 The peak intensity Ig ratio Id / Ig is 0.2-0.

35.

4. The graphite negative electrode active material according to any one of claims 1 to 3, characterized in that Based on the total number of particles of the graphite negative electrode active material, the number of primary particles in the graphite negative electrode active material accounts for greater than or equal to 85%, and can be optionally 85%-100%.

5. The graphite negative electrode active material according to any one of claims 1 to 4, characterized in that The graphitization degree of the graphite negative electrode active material is 85%-91%.

6. The graphite negative electrode active material according to any one of claims 1 to 5, characterized in that The volume distribution particle size Dv50 of the graphite negative electrode active material is less than or equal to 15.0 μm, and can be optionally 9.0 μm-14.0 μm.

7. The graphite negative electrode active material according to any one of claims 1 to 6, characterized in that The graphite negative electrode active material comprises a core and a coating layer at least covering the surface of the core, the core is artificial graphite, and the coating layer comprises amorphous carbon.

8. The graphite negative electrode active material according to any one of claims 1 to 7, characterized in that The graphite negative electrode active material satisfies at least one of the following conditions: (1) The tap density of the graphite negative electrode active material is 1.0 g / cm 3 -1.4g / cm 3 ; (2) The specific surface area of ​​the graphite negative electrode active material is 0.75 m 2 / g-1.75m 2 / g; (3) The particle size distribution of the graphite negative electrode active material (Dv90-Dv10) / Dv50 is 1.30-1.80; (4) The gram capacity of the graphite negative electrode active material is 325 mAh / g-340 mAh / g.

9. A method for preparing a graphite negative electrode active material, characterized in that: The steps include: Provide raw materials; Processing the raw material to obtain a precursor; The precursor is graphitized to obtain a graphitized product; The graphitized product is subjected to surface treatment to obtain a graphite negative electrode active material. The powder compaction density of the graphite negative electrode active material under a pressure of 49000N is greater than or equal to 1.60g / cm 3 ; In the Raman spectrum of the graphite negative electrode active material, 1250 cm -1 Up to 1500cm -1 The peak intensity Id and 1500cm -1 Up to 1650cm -1 The peak intensity Ig ratio Id / Ig is greater than or equal to 0.

15.

10. The preparation method according to claim 9, characterized in that: The surface treatment specifically comprises the following steps: The graphitized product is subjected to a fusion treatment to obtain an intermediate, wherein the frequency of the fusion treatment is 20-40 Hz, and / or the time of the fusion treatment is 5-15 min; The intermediate is mixed with asphalt at room temperature and then carbonized to obtain a graphite negative electrode active material.

11. The preparation method according to claim 10, characterized in that: The mass ratio of the intermediate to asphalt is 1:99-10:90, and can be optionally 2:98-5:

95.

12. The preparation method according to any one of claims 9 to 11, characterized in that: The raw material comprises one or more of petroleum coke, needle coke, and pitch coke, and petroleum coke can be selected.

13. The preparation method according to claim 12, characterized in that: Based on the total volume of the raw material structure, the volume proportion of the mosaic structure and the regional structure is greater than or equal to 60%, and can be optionally 65%-80%.

14. The preparation method according to any one of claims 9 to 13, characterized in that: The maximum power of the graphitization treatment is 70%-90% of the rated power of the graphitization treatment equipment.

15. The preparation method according to any one of claims 9 to 14, characterized in that: The maximum power of the graphitization treatment is 21000W-26000W; and / or the constant power time of the graphitization treatment at the maximum power is 8h-40h.

16. The preparation method according to any one of claims 9 to 15, characterized in that: The gram capacity of the graphitized product is 325-340 mAh / g.

17. The preparation method according to any one of claims 9 to 16, characterized in that: The processing of raw materials specifically comprises the following steps: The raw materials are crushed, shaped, and graded, and fine powder after crushing is removed to obtain secondary raw materials; Carbonizing the secondary raw material to obtain a precursor, Wherein, the volume distribution particle size Dv50 of the secondary raw material is 8.0-16.0 μm, and / or the particle size distribution (Dv90-Dv10) / Dv50 of the secondary raw material is 1.30-1.

70.

18. A secondary battery, comprising a negative electrode plate, characterized in that: The negative electrode sheet comprises the graphite negative electrode active material according to any one of claims 1 to 8 or the graphite negative electrode active material prepared by the preparation method according to any one of claims 9 to 17.

19. An electrical device, characterized in that: Includes the secondary battery as claimed in claim 18.

Citation Information

Patent Citations

  • Lithium ion battery and cathode material thereof

    CN108155351A

  • Secondary battery, battery module including same, battery pack, and device

    CN114902450A

  • Negative electrode material, negative electrode plate, electrochemical device and electronic device

    CN116706076A

  • Negative electrode active material, electrochemical device, and electronic apparatus

    JP2023153876A

  • Artificial graphite, secondary battery, method for the preparation thereof, and apparatus

    US20210399301A1

Cited By

  • Graphite negative electrode active material and preparation method therefor, secondary battery containing same and electric device

    EP4815054A1